Performance of equity mutual funds in Thailand - Rujivipat, Anutra (2018)
This dissertation examines the performance of 242 open-ended equity mutual funds in Thailand from January 2009 to December 2017 by employing the Jensen’s measure, the Fama-French’s Three-factor model, and the Carhart’s Four-factor model. The overall results show that market risk premium, firm size, and momentum factors can largely explain the time-series variation in equity fund returns, and the Carhart’s Four-factor model is the most effective among all models. Using the net returns of these funds, the results of a value-weighted portfolio under the Carhart’s Four-factor model suggest that, on average, they outperform the market benchmark by 1.92% p.a. with a slightly lower systematic risk. Besides, evidence from individual fund analysis shows that 72 of out of these 242 funds can successfully beat the market. In addition, this study documents the small market timing skill of fund managers under the Treynor and Mazuy model. This indicates that the funds may have superior returns mainly because they follow the momentum trading strategy of buying past winner stocks and selling past loser stocks. Another reason may be due to the capability of fund managers to frequently outguess the market correctly. Apart from the performance analysis, this study investigates whether or not Thai equity funds exhibit persistence in performance. The results suggest that performance persistence does not exist because of last year’s bottom-performing funds, which possess a significantly positive timing ability and thus, overcome the past winners in the following year. Moreover, fund managers of last year’s top- performing funds may not rebalance their portfolio much so merely by chance they still hold good stocks in the following year. However, persistence does not last long since this return anomaly is eliminated once the market realises it. As a result, they are no longer at the top position in a year later.